Alcohol modulation of G-protein-gated inwardly rectifying potassium channels: from binding to therapeutics - Bodhinathan, Karthik; Slesinger, Paul A. (Frontiers in Physiology, 2014)
Alcohol (ethanol)-induced behaviors arise from direct interaction of alcohol with discrete protein cavities within brain proteins. Recent structural and biochemical studies have provided new insights into the mechanism of alcohol-dependent activation of G protein-gated inwardly rectifying potassium (GIRK) channels, which regulate neuronal responses in the brain reward circuit. GIRK channels contain an alcohol binding pocket formed at the interface of two adjacent channel subunits. Here, we discuss the physiochemical properties of the alcohol pocket and the roles of G protein G subunits and membrane phospholipid PIP2 in regulating the alcohol response of GIRK channels. Some of the features of alcohol modulation of GIRK channels may be common to other alcohol-sensitive brain proteins. We discuss the possibility of alcohol-selective therapeutics that block alcohol access to the pocket. Understanding alcohol recognition and modulation of brain proteins is essential for development of therapeutics for alcohol abuse and addiction.